2017
DOI: 10.1038/srep40594
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for microtubule-independent dimerization of TPPP/p25

Abstract: Tubulin Polymerization Promoting Protein (TPPP/p25) is a brain-specific disordered protein that modulates the dynamics and stability of the microtubule network by its assembly promoting, cross-linking and acetylation enhancing activities. In normal brain it is expressed primarily in differentiated oligodendrocytes; however, at pathological conditions it is enriched in inclusions of both neurons and oligodendrocytes characteristic for Parkinson’s disease and multiple system atrophy, respectively. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…Control experiments revealed that neither the empty Venus vectors [42] nor the Venus fusion constructs of LC8-2 and -synuclein produce a BiFC signal ( Supplementary Fig. 7A), that concerns with the in vitro ELISA data (cf.…”
Section: Interactions Of Lc8-2 In Living Cellsmentioning
confidence: 89%
See 2 more Smart Citations
“…Control experiments revealed that neither the empty Venus vectors [42] nor the Venus fusion constructs of LC8-2 and -synuclein produce a BiFC signal ( Supplementary Fig. 7A), that concerns with the in vitro ELISA data (cf.…”
Section: Interactions Of Lc8-2 In Living Cellsmentioning
confidence: 89%
“…The BiFC plasmids (pBiFC-V N1-173 , pBiFC-V C155-238 ) were a gift of Prof. Péter Várnai (Semmelweis University, Budapest). The V N -TPPP/p25 plasmid containing the insert for human FL TPPP/p25 was prepared as described previously [42]. Plasmid V C -LC8-2 was produced by inserting the LC8-2 coding region in frame into pBiFC-V C155-238 by EcoRI and SalI restriction enzymes.…”
Section: Bimolecular Fluorescence Complementation (Bifc) Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BiFC plasmids (pBiFC-VN1-173, pBiFC-VC155-238) were a gift of Prof. Péter Várnai (Semmelweis University, Budapest). The V C -TPPP/p25 plasmid containing the insert for human full length TPPP/p25 was prepared as described previously 14 , 43 . Plasmid V N -SIRT2 was produced by inserting the SIRT2 coding region in frame 25 into pBiFC-VN1-173 by XhoI and BamHI restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 7 variants were localized in genes involved in the cytoskeleton (MAST4, TPPP), iron homeostasis (FTMT), lysosomal degradation of sulfate esters (IDS), glutamate carboxypeptidases (NAALADL2), and fertility according to their sole expression in reproductive organs (DSCR4, SPATA19). Of these, MAST4 [62], TPPP [63], FTMT [64], and IDS [65] have been linked to pathological processes in the brain.…”
Section: Discussionmentioning
confidence: 99%